Antara Idola dan Konsumsi: Hubungan Parasocial Relationship dengan Perilaku Konsumtif Penggemar K-pop di Surabaya - Makhfufa, Mita Amaliya; Arifiana, Isrida Yul; Efendy, Mamang (JIWA: Jurnal Psikologi Indonesia, 2024)
Social media interactions allow fans to feel closer and more connected to their idols, even though these interactions are only virtual and one-sided, known as parasocial relationships. This relationship can build an emotional bond between idols and fans, which can encourage fans to spend money as a form of support for their idols, such as purchasing merchandise, albums, concert tickets, or branded items worn by the idols. This study aims to determine the relationship between parasocial relationships and consumptive behavior among K-pop fans in Surabaya. The research uses a correlational quantitative method with 256 K-pop fans in Surabaya as respondents, selected using purposive sampling with criteria explained during the data collection. The research scales used include a consumptive behavior scale with a Cronbach's alpha value of 0.941 and a parasocial relationship scale with a Cronbach's alpha value of 0.921, indicating good psychometric quality. Data analysis was performed using the Pearson Product Moment parametric correlation technique with the IBM SPSS 25.0 for Windows software. The results of the study show a significant positive relationship between parasocial relationships and consumptive behavior. Therefore, the hypothesis in this study is accepted. This means that the higher the parasocial relationship behavior, the higher the consumptive behavior among K-pop fans in Surabaya. Keywords: Consumptive Behaviour, Parasocial Relationships, K-pop Fans